Commemoration, Representation and Interpretation: Augustine of Hippo’s Depictions of the Martyrs - Martin, Elena (Studies in church history, 2011)
Recent studies of martyrdom in early Christianity look beyond the traditional perception of martyr acta and passiones as historical documents that can help us to reconstruct the past. While previously these texts had been deemed worthy of attention on account of their proven authenticity or historical veracity, now they are all valued as important sources that have much to tell us about the communities and environments in which they were produced. This approach does not deny the historical value of the sources, but rather it appreciates that they are a special kind of historical document. Texts and sermons about holy men and women never were created as objective accounts. Every textual portrait of a martyr reveals a prior judgement that inscribes meaning and purpose into seemingly meaningless events to present condemned criminals as religious heroes, horrific tortures as divine gifts, and public deaths as cosmic dramas. Consequently, the various methods of representation that were used to construct depictions of the martyrs are significant elements in their own right, whether they are rhetorical devices, scriptural allusions, artistic embellishments or miraculous occurrences. These are the very details that make martyrs; they turn death into martyrdom, and the dead into martyrs.